Strain selection, growth productivity and biomass characterization of novel microalgae isolated from fresh and wastewaters of upper Punjab, Pakistan. Issue 3 (2nd July 2016) - Gill, Saba Shahid; Mehmood, Muhammad Aamer; Ahmad, Niaz; Ibrahim, Muhammad; Rashid, Umer; Ali, Shafaqat; Nehdi, Imededdine Arbi
ABSTRACT: The present study was focussed on selection of fast-growing microalgae with higher lipid content using cheaper growth media, aimed to reduce the cost of algal biomass production. Samples were collected from 40 different sites from fresh and wastewater bodies. Based on morphological differences, two microalgae (SSG and SA) from wastewater and three (OP, DFM and JRC) from fresh water habitat were selected for further characterization. The specific growth rates (g Day −1 L −1 ) of the OP, DFM, JRC, SA and SSG were found to be 0.614, 0.638, 0.734, 1.06 and 1.02, respectively, whereas the doubling time ( Td ) was shown to be as 39.30, 36.48, 22.08, 12.24 and 12.98 h, respectively, when cultured without controlled temperature and CO2 supply, in a locally designed photobioreactor. All five microalgae shown considerable growth at a range of pH 6.0–9.0 with a peak activity within pH range 7.5–8.5. The OP, DFM and JRC contained 27%, whereas SSG and SA shown 39% lipid content. The phylogenetic analyses based on the 18S rRNA gene sequence have shown that studied microalgal strains may be novel species.